Microwave assisted preparation of LiFePO4/C coated LiMn1.6Ni0.4O4 for Li-ion batteries with superior electrochemical properties (2022)
ABSTRACT: LiMn1.6Ni0.4O4 (LMNO) spinel is a promising cobalt-free electrode for high potential applications. However, its chemical stability against electrolytes is relatively poor. Inorganic coatings have widely used to achieve superior chemical and electrochemical properties. A promising example is LiFePO4/C (LFP/C) olivine coated LMNO spinel particles, in which olivine provides a high chemical stability. Chemical incompatibility between them during atmospheric synthesis conditions makes the process extremely challenging. Herein, we propose a simple and practical route to prepare LFP/C-coated LMNO using microwave irradiation. This process significantly improves the crystallographic order of the spinel structure and provides sufficient physical interaction between both materials while avoiding side reactions. Li-ion battery using LFP/C-coated LMNO electrode exhibits a higher discharge capacity at 25°C and 60°C than those of uncoated spinel. Moreover, cyclability (up to 500 cycles) at 25°C and C-rate capability performances at 60°C are superior in LFP/C-coated LMNO particles and not possible using uncoated spinel.